The impact of fibre connectivity on SMEs : benefits and business opportunities - Phippen, Andy; Lacohée, Hazel (Palgrave pivot., 2017)
Drawing on research conducted over the last 3 years in Cornwall, UK, this new book explores the impact of the EU/BT funded introduction of fibre broadband on rural SMEs. Including a qualitative methodology and in depth focus groups with over 200 companies, The Impact of Fibre Connectivity on SMEs provides a detailed, in depth, analysis to challenge conventionally held beliefs in the value of subsidy and policy pressure in the deployment of such projects. With focus on regional development in the UK as well as exploration of the wider EU context, the book presents a genuine insight into the technology adoption and technology provision. Andy Phippen is Professor of Social Responsibility in IT at Plymouth Plymouth Business School, Plymouth University, UK. He has conducted empirical research into the relationship between technology and public engagement for over 15 years, including work into public trust in online systems, young people and privacy, and the impact of technologies in rural locations. Hazel Lacohée undertakes qualitative research on behalf of BT TSO within the People and Behaviours Research team. She joined BT in 1998 and is responsible for providing insight regarding the commercial, socio-economic and customer impact of ICT applications and systems. Hazel obtained an ESRC funded PhD in Psychology from the University of Bristol in 1996 and her current work concerns the impact of NGA for Businesses and Consumer.